Upregulation of Atypical Cadherin FAT1 Promotes an Immunosuppressive Tumor Microenvironment via TGF-β - Irshad, Khushboo; Srivastava, Chitrangda; Malik, Nargis; Arora, Manvi; Gupta, Yakhlesh; Goswami, Sanjeev; Sarkar, Chitra; Suri, Vaishali; Mahajan, Swati; Gupta, Deepak Kumar; Suri, Ashish; Chattopadhyay, Parthaprasad; et al. (Frontiers in Immunology, 2022)
FAT atypical cadherin 1 (FAT1) promotes glioblastoma (GBM) by promoting protumorigenic inflammatory cytokine expression in tumor cells. However, tumors also have an immunosuppressive microenvironment maintained by mediators such as transforming growth factor (TGF)-β cytokines. Here, we have studied the role of FAT1 in tumor immune suppression. Our preliminary TIMER2.0 analysis of The Cancer Genome Atlas (TCGA) database revealed an inverse correlation of FAT1 expression with infiltration of tumor-inhibiting immune cells (such as monocytes and T cells) and a positive correlation with tumor-promoting immune cells [such as myeloid-derived suppressor cells (MDSCs)] in various cancers. We have analyzed the role of FAT1 in modulating the expression of TGF-β1/2 in resected human gliomas, primary glioma cultures, and other cancer cell lines (U87MG, HepG2, Panc-1, and HeLa). Positive correlations of gene expression of FAT1 and TGF-β1/2 were observed in various cancers in TCGA, Glioma Longitudinal Analysis Consortium (GLASS), and Chinese Glioma Genome Atlas (CGGA) databases. Positive expression correlations of FAT1 were also found with TGF-β1/2 and Serpine1 (downstream target) in fresh-frozen GBM samples using q-PCR. siRNA-mediated FAT1 knockdown in cancer cell lines and in primary cultures led to decreased TGF-β1/2 expression/secretion as assessed by q-PCR, Western blotting, and ELISA. There was increased chemotaxis (transmigration) of THP-1 monocytes toward siFAT1-transfected tumor cell supernatant as a consequence of decreased TGF-β1/2 secretion. Reduced TGF-β1 expression was also observed in THP-1 cultured in conditioned media from FAT1-depleted glioma cells, thus contributing to immune suppression. In U87MG cells, decreased TGF-β1 upon FAT1 knockdown was mediated by miR-663a, a known modulator. FAT1 expression was also observed to correlate positively with the expression of surrogate markers of MDSCs [programmed death ligand-1 (PD-L1), PD-L2, and interleukin (IL)-10] in glioma tumors, suggesting a potential role of FAT1 in MDSC-mediated immunosuppression. Hence, our findings elaborate contributions of FAT1 to immune evasion, where FAT1 enables an immunosuppressive microenvironment in GBM and other cancers via TGF-β1/2.